Re-conceiving Afghan cellular architecture for the reconstruction of rural schools - Watts, Donald J.; Yoldas, Cenk (Center for Environmental Design Research, University of California at Berkeley, 2009)
Afghanistan suffers from a quarter century of war that has resulted in a devastated infrastructure and a generation of Afghans who have lived without a local school. This paper presents an architectural design investigation that seeks ways of synthesizing traditional social-cultural and formalspatial attributes with refined material and construction capabilities becoming increasingly available worldwide. In the spirit of George Kubler's thesis of invention and variation, stabilized compressed brick construction and computer aided structural analysis are introduced as refinements within the Afghan building tradition.
Keywords: Afghanistan; Architecture; Schools; Compressed brick; Vernacular transformation